(untitled) (Innovative professional education, 2024)
The article states the importance of cooperation and responsible partnership for the development of vocational education and the national qualifications system; outlines the trends in the development of public-private partnership in vocational education; characterizes the possibilities of harmonizing the regulatory and legal support for the development of public-private partnership in vocational education with European legislation.